2020
DOI: 10.1021/acs.biomac.0c00357
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Electron-Demand Diels–Alder Methylcellulose Hydrogels Enable the Co-delivery of Chondroitinase ABC and Neural Progenitor Cells

Abstract: A hydrogel that can deliver both proteins and cells enables the local microenvironment of transplanted cells to be manipulated with a single injection. Toward this goal, we designed a hydrogel suitable for the co-delivery of neural stem cells and chondroitinase ABC (ChABC), a potent enzyme that degrades the glial scar that forms after central nervous system (CNS) injury. We leveraged the inverse electron-demand Diels−Alder reaction between norbornene and methylphenyltetrazine to form rapidly gelling (<15 min) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…To facilitate complete protein release, we are further engineering the MC delivery vehicle to expedite degradation and resorption in vivo. We have recently synthesized a resorbable MC hydrogel with a disulfide-containing cross-linker, which enables material degradation in the presence of naturally occurring thiols in vivo ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate complete protein release, we are further engineering the MC delivery vehicle to expedite degradation and resorption in vivo. We have recently synthesized a resorbable MC hydrogel with a disulfide-containing cross-linker, which enables material degradation in the presence of naturally occurring thiols in vivo ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate complete protein release, we are further engineering the MC delivery vehicle to expedite degradation and resorption in vivo. We have recently synthesized a resorbable MC hydrogel with a disulfide-containing cross-linker, which enables material degradation in the presence of naturally occurring thiols in vivo (33). The modifications to ChABC described here have improved its production, stability, and long-term bioactivity, overcoming many challenges required for clinical translation and facilitating its future use as a viable therapeutic in treating CNS injuries.…”
Section: Chondroitin Sulfate a Dermatan Sulfatementioning
confidence: 99%
“…The use of gelatin as backbone polymer to form the hydrogels allows a better mimicking of the native ECM, thanks to the ECM biomimetic motifs naturally present in gelatin. When other polymers (e.g., alginate, 36 PEG, 35 and methylcellulose) 38 were used to prepare hydrogels by Tz-Nb crosslinking, an additional synthesis step was required to artificially introduce ECM biomimetic motifs to improve their biological performance. Conversely, it was previously demonstrated 44 that gelatin hydrogels modified by Tz-Nb, even with higher degrees of modification, maintain their cell-adhesive and MMP-degradable peptide sequences, thus avoiding the need for further modification to impart these properties on the hydrogels.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bioorthogonal cross-linking strategies include azide–alkyne cycloaddition, nitrile oxide cycloaddition, Diels–Alder reactions, and inverse-electron demand Diels–Alder reactions . The latter has been investigated by using, for instance, the reaction between tetrazine (Tz) and norbornene (Nb), which has been demonstrated as being successful for the preparation of hydrogels based on PEG, alginate, hyaluronan, methylcellulose, and different polymer combinations. In recent work, the suitability of this bioorthogonal cross-linking strategy was investigated for the first time for cell-laden gelatin hydrogels . The authors prepared two different gelatin derivatives, functionalized either with Tz or Nb, with a similar degree of modification (i.e., approximately 20%), and mixed them to form gelatin hydrogels at different gelatin concentrations (i.e., 5 and 10%).…”
Section: Introductionmentioning
confidence: 99%
“…also exploited the thiol‐disulfide dynamic exchange by inserting ‐SS‐ bonds in inverse‐electron demand Diels–Alder crosslinked hydrogels, which enabled hydrogel degradation with glutathione, thereby enabling the delivery of cells and enzymes in vivo. [ 214 ] In another study, it was shown that thiolated HA gelled quickly with oxidized glutathione, remained stable for at least 10 days of in vitro culture, and allowed proliferation of adipose‐derived stem cells. [ 215 ]…”
Section: Case Studies Of 3d Cell Culture In DCC Hydrogelsmentioning
confidence: 99%